PENGARUH SENAM HAMIL TERHADAP PENURUNAN SKALA NYERI PUNGGUNG PADA IBU HAMIL TRIMESTER II DAN III DI BPM NY. IMMATUS SHOLEHAH, Amd.Keb DI DESA KEBONAGUNGÂ KEC.UJUNGPANGKAH KAB. GRESIK - Purwati, Heni; Fajriyani Agustina, Ani (JURNAL KEPERAWATAN BINA SEHAT, 2016)
Back pain is a discomfort condution in pregnat women that distrubed in perfoming daily activities. As long during the situation can make back pain scale is in creasing one of therapy that can reduce pain scale is pregnancy exercise because pregnancy exercise can make elastic muscles and ligament in the pelvis and train the transverse abdominak muscletone which is a supporting part in the main posturat of the spine, so it is able to reduce back pain scale. The purpose of this study to analyze the effect of pregnancy exercise on reducing back pain scale in pregnancy women TM II and TM III. The research method is used one group pre test-post test design. With a total population of 15 responden and the sampling technique used is non probably sampling with purposive sampling and get a sample of 13 respondents. The research instruments is used pain observation scale sheet. The result of research is before doing pregnancy exercise as much as 7 pregnant women get back pain scale light and after doing pregnancy exercise as much as 8 pregnant women do not have back pain using SPSS 16.0 version is known that p value (0,001) <α (0,05) with the research result showed H1accepted, thus there is influence pregnancy exercise on reducing back pain scale in pregnant women TM II dan TM III inBPM Ny.Immatus Sholehah, Amd.Keb Kebonagung Ujungpangkah Gresik. So there is a decrease back pain scale in pregnant women TM II and TM III if doing pregnancy exercise according to SOP.Keywords : Pregnancy exercise, back pain scale, and pregnant women.